2008
DOI: 10.11646/zootaxa.1868.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Pupal cases of Nearctic robber flies (Diptera: Asilidae)

Abstract: The literature on robber fly pupae published primarily since 1972 is reviewed. Terminology used in morphological descriptions of pupal cases is compared and standardized, and some new terminology is used. A general description of asilid pupal cases is presented. Diagnostically useful characters are identified, and a consistent format for descriptions is presented. Pupal cases of 24 species are described for the first time, those of 13 species are redescribed, and additional comments are made on the pupal cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Melin (1923) indicated, based on the pupae of six species of Laphria, that the hypopharyngeal sheath (now designated the proboscial sheath) on pupae of the subfamily Laphriinae extends to the heartshaped piece or posterior coxal sheath. Dennis et al (2008a) also showed this for seven species of Laphria and Lampria bicolor (Wiedemann). However, this is not true for A. atrum, A. bayardi, or A. albopilosum.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…Melin (1923) indicated, based on the pupae of six species of Laphria, that the hypopharyngeal sheath (now designated the proboscial sheath) on pupae of the subfamily Laphriinae extends to the heartshaped piece or posterior coxal sheath. Dennis et al (2008a) also showed this for seven species of Laphria and Lampria bicolor (Wiedemann). However, this is not true for A. atrum, A. bayardi, or A. albopilosum.…”
Section: Resultsmentioning
confidence: 67%
“…The dorsolateral processes are basally large on A. bayardi; on A. atrum and A. albopilosum, the ventrolateral processes are basally even larger or thicker. Dennis et al (2008a) and Melin (1923) found that male pupal cases can be distinguished from female cases by the presence of midventral callosities on the ninth abdominal segment. These callosities are present on the male pupal case of…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The shape of the mandibles and maxillae are important in larval taxonomy, as are the presence or absence of fleshy tubercles on the abdominal segments and the presence or absence of a sclerotised plate on the last abdominal segment (Foote and Dennis 1991). The precise number, shape and curvature of the sclerotized processes on the head and thorax of the pupae, and the nature and number of the spines and spurs on the pupal abdomen, as well as the shape and curvature of the processes on abdominal segment nine are important in pupal taxonomy (Dennis et al 2008).…”
Section: Introductionmentioning
confidence: 99%